Characteristics of Paraffin Shielding of Kartini Reactor, Yogyakarta - Lana Khanifah; Susilo Widodo; Widarto; Ngurah Made Dharma Putra; Argo Satrio (ASEAN Journal on Science and Technology for Development, 2018)
The National Nuclear Energy Agency (BATAN) Yogyakarta uses two kinds of paraffin for shielding radiation of Kartini reactor. For developing BNCT research, the radiation attenuation capability of paraffin has been analyzed to find out the coefficient attenuation, density, and composition of both kinds of paraffin. The components of the paraffin were analyzed using Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy characterization. Paraffin P1 has a density of 0.689 gr/mL and paraffin P2 is 0.578 gr/mL. Paraffin samples P1 and P2 were the sample content of functional group CH, CH2, and OH when analyzed by FTIR. Paraffin P2 had an additional content namely CO. The concentration of carbon (C) and oxide (O) of paraffin P2 was much greater than that of paraffin P1. Hydrogen (H) in the paraffin has the function of moderating neutrons, but hydrogen content in both kinds of paraffin could not be detected by EDX. The acquired neutron coefficient attenuation of paraffin P2 was 0.0382 cm-1 and the gamma coefficient attenuation was 0.0535 cm-1.